One cannot make ommellette without breaking the eggs: a glimpse on the level of familiarity with OPAC utilisation among university students - M Said, Salasiah; Abdul Rahman, Abd Latif; Rosman, Nurul Ain Azzaliah (Universiti Teknologi MARA, Kedah, 2024)
The development of the Online Public Access Catalogue (OPAC) can be attributed to the collaborative work of Frederick Kilgour and Henriette Davidson Avram during the 1960s. The proliferation of online catalogues in libraries nationwide can be attributed to the advent of new systems and rising technology, which have rekindled interest in the development of Online Public Access Catalogues (OPACs).